A descriptive summary of the WHO availability assessments of medical abortion medicines in eight African countries - Amy Grossman; Ndola Prata; Sarah Jones; Laurence Läser; Bela Ganatra; Antonella Lavelanet; Natalie Williams; Chilanga Asmani; Hayfa Elamin; Leopold Ouedraogo; Lucy Sejo Maribe; Dina Vladimirovna Gbenou; et al. (Reproductive Health)
Abstract Background The use of medical abortion using either a combination of mifepristone and misoprostol, or misoprostol alone has contributed to increased safety and decreased mortality and morbidity. The availability of quality medical abortion medicines is an essential component in the provision of quality abortion care. Understanding the factors that influence the availability of medical abortion medicines is important to help in-country policymakers, program planners, and providers improve availability and use of medical abortion. Methods Using a national assessment protocol and an availability framework, we assessed the availability of medical abortion medicines across five elements (Registration & Quality Assurance, Policy & Financing, Procurement & Distribution, Provider Knowledge, and End-user Knowledge) in eight countries: Botswana, Burkina Faso, Central African Republic, Democratic Republic of the Congo, Eswatini, Lesotho, Namibia and Uganda between November 2020 and November 2021. The assessment included an online desk review and virtual or telephone-based key informant interviews. Results Registration of medical abortion medicines—misoprostol or co-packaged mifepristone and misoprostol products (combi-pack)—was established in all countries, except the Central African Republic. In Lesotho and Eswatini, the national regulatory agency is still in development and importation of Cytotec™ misoprostol is permitted for off-label use in obstetrics/gynecology. Misoprostol was included in all countries’ essential medicines lists, except Botswana. Burkina Faso and Democratic Republic of the Congo also include mifepristone on their essential medicines list and medical abortion regimens in national abortion care service and delivery guidelines. Additionally, guidelines clarified health worker roles in the provision of abortion care specific to the legal context of each country and permitted task-shifting of abortion service provision. Where guidelines did not exist, medical abortion medicines and their use were not well integrated into the public health care system. Community awareness activities on abortion rights and services have been limited in scope across the countries assessed, however, end-users' awareness of misoprostol as a medical abortion medicine was reported. Conclusion The national landscape assessments identified several cross-cutting opportunities to improve availability of medical abortion medicines, including importing quality-assured medical abortion medicines; developing nationally approved abortion service and delivery guidelines that optimize healthcare worker roles; and expanding communication strategies to reach end-users and pharmacists.